Geophysical Responses from Mineral System Components in the Deep Crust and Upper Mantle. Issue 1 (1st December 2016) - Dentith, Michael
Abstract : The concept of a mineral deposit forming via a mineral system that operates across areas of perhaps 1000s of squares kilometres and to mantle depths has important implications for greenfields mineral exploration. Geographically widespread datasets and deep penetrating geophysical methods are required to map key mineral system elements such as fluid/metal source zones and migration paths. Developed primarily for academic studies of the deep crust, there are several established geophysical techniques that can potentially be used to identify elements of mineral systems in the deep crust and upper mantle. Although the seismic reflection method produces the highest quality images, it is prohibitively expensive and the recommended approach is a combination of MT surveys and receiver function recordings with CCP stacking. Mineral system elements that can be detected in this fashion include major structures and geological boundaries which are potential controls on fluid flow and also areas of crust and mantle that have been altered by one or both of fluid creation and migration